2022
DOI: 10.3390/gels8020109
|View full text |Cite
|
Sign up to set email alerts
|

Application of Alginate-Based Hydrogels in Hemostasis

Abstract: Hemorrhage, as a common trauma injury and clinical postoperative complication, may cause serious damage to the body, especially for patients with huge blood loss and coagulation dysfunction. Timely and effective hemostasis and avoidance of bleeding are of great significance for reducing body damage and improving the survival rate and quality of life of patients. Alginate is considered to be an excellent hemostatic polymer-based biomaterial due to its excellent biocompatibility, biodegradability, non-toxicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 154 publications
0
33
0
Order By: Relevance
“…This was attributed to multiple reasons as hydrogels are three-dimensional structures that provide optimum moisture, mimic the skin, act as a barrier for invading microorganism, and, more importantly, can be easily removed from wounds without damaging underlying cells (Khan et al, 2021). Furthermore, sodium alginate also contributes Frontiers in Bioengineering and Biotechnology frontiersin.org to hemostasis and wound healing due to good biocompatibility, mucoadhesion, high swelling, and oxygen permeability (Aderibigbe and Buyana, 2018;Xie et al, 2022). The literature survey revealed that phytochemical constituents, such as flavonoids and triterpenoids, are known to promote the wound healing process owing to astringent and antimicrobial properties.…”
Section: Antioxidant Assaymentioning
confidence: 99%
“…This was attributed to multiple reasons as hydrogels are three-dimensional structures that provide optimum moisture, mimic the skin, act as a barrier for invading microorganism, and, more importantly, can be easily removed from wounds without damaging underlying cells (Khan et al, 2021). Furthermore, sodium alginate also contributes Frontiers in Bioengineering and Biotechnology frontiersin.org to hemostasis and wound healing due to good biocompatibility, mucoadhesion, high swelling, and oxygen permeability (Aderibigbe and Buyana, 2018;Xie et al, 2022). The literature survey revealed that phytochemical constituents, such as flavonoids and triterpenoids, are known to promote the wound healing process owing to astringent and antimicrobial properties.…”
Section: Antioxidant Assaymentioning
confidence: 99%
“…Alginate is a natural anionic polymer derived mainly from brown algae found in the ocean. Alginate is a copolymer with L-gulo-glucuronide (G) and D-mannuronic acid (M) structural units with either continuous G chain segments (GGGG) and M chain segments (MMMM) or alternating MGMG chain segments [ 168 , 169 ]. It is currently believed that only the G unit is involved in the multivalent ion-induced crosslinking of alginate and that a high G content can improve the mechanical strength of a hydrogel.…”
Section: Advanced Polymer Hydrogels For Dusmentioning
confidence: 99%
“…79 At the same time, the hemostatic properties of alginate-based hydrogels make them an ideal platform in the treatment of postoperative resection. 80,81 With the addition of Ca 2+ , SA can be cross-linked with Ca 2+ to form the hydrogel immediately. Due to its convenience and biosafety, injectable SA hydrogels were employed for adjuvant immunotherapy in the prevention of post-surgical tumor relapse in Zhang et al's work.…”
Section: Natural Polymer-based Hydrogelsmentioning
confidence: 99%